PENGARUH MODEL PEMBELAJARAN MAKE A MATCH DAN MOTIVASI SISWA TERHADAP HASIL BELAJAR SISWA PADA MATERI FARAIDH - manopo, riska (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2025)
This research aims to explore the make match learning model and student motivation in improving learning outcomes for Faraidh material at the school of Madrasah Aliyah Imam Adil in Raja Ampat. This research uses a quantitative approach, namely an experimental pretest-posttest design, by giving a pre-test and post-test to two groups, the conventional group as the control and the experimental group. Data analysis was carried out descriptively using the t test and anova (two-way analysis of variance). The data was processed using SPSS version 25 for Windows to get a comparison of the results of fiqh learning on Faraidh (inheritance) material and its motivation. The research results showed that there was a significant increase in student achievement and learning motivation with the make match model applied to the experimental group, where an average increase of 50 to 70 points from pretest to posttest scores, while the conventional group only had an average increase of 10 points. The make match and motivation learning models have a symmetrical or parallel influence on improving student learning outcomes, as in the data findings in table 4.5; 4.6; 4.7; and 4.8, and is supported by the findings of the 2-factor Anova test results depicted in figure 4.1, and figure 4.2 in the data blockspot normality test.